PENYULUHAN TENTANG KHASIAT DAN PEMANFAATAN SAWI TANAH MENJADI MINUMAN TEH DAN BAHAN-BAHAN ALAMI LAINNYA DI KELURAHAN SUMBER JAYA - Jannah, Syauqul; Herlina, Herlina; Alfitroh, Ijazati (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
This study aims to propose a health promotion program related to the production of herbal tea from turnip greens (Brassica rapa L.). Turnip greens are known for their high nutritional content and health benefits, including antioxidants, vitamins, and minerals. The program will involve promotional activities focusing on educating the public about the health benefits of consuming turnip green herbal tea, as well as marketing this product as a healthy beverage alternative. The outcomes of this program are expected to enhance public awareness of the health benefits associated with consuming turnip green herbal tea and facilitate access to high- quality, locally sourced herbal health products. Therefore, this program is anticipated to contribute positively to promoting healthier consumption patterns in the community.